2023
DOI: 10.1002/csc2.20983
|View full text |Cite
|
Sign up to set email alerts
|

Development of maize inbred lines with elevated grain methionine concentration from a high methionine population

Abstract: Methionine is a nutritionally limiting amino acid in poultry diets based on maize (Zea mays L.) grain. Synthetic dietary supplements are available but are costly and not preferred by organic poultry producers. The development of high methionine maize varieties would reduce the need for supplementation. Several approaches have been reported for achieving this goal. Here, we report a novel approach that can produce diverse inbred lines with higher content of methionine than other methods. Inbred lines were devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(41 reference statements)
1
4
0
Order By: Relevance
“…Significant genotypic variation observed for methionine suggested the presence of adequate genotypic variability for effective selection, enhancement of germplasm, and development of improved hybrids (Ali et al, 2011). In agreement with our findings, Hintch et al (2023) also reported a significant G × E interaction for grain methionine. However, our results suggested that contributions from the environment and G × E interactions to the total variation were of low and negligible magnitude, thereby suggesting that the methionine concentration is less likely to be affected by environments.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Significant genotypic variation observed for methionine suggested the presence of adequate genotypic variability for effective selection, enhancement of germplasm, and development of improved hybrids (Ali et al, 2011). In agreement with our findings, Hintch et al (2023) also reported a significant G × E interaction for grain methionine. However, our results suggested that contributions from the environment and G × E interactions to the total variation were of low and negligible magnitude, thereby suggesting that the methionine concentration is less likely to be affected by environments.…”
Section: Discussionsupporting
confidence: 94%
“…Erdal et al (2019), who carried out a study on a set of 73 inbreds, reported a variation of 0.17%-0.22%, with a mean of 0.19% methionine. Recently, Hintch et al (2023) reported that the methionine concentration among the maize inbreds varied from 0.20% to 0.37%. Various genes have been considered to be involved in the higher accumulation of methionine in maize.…”
Section: Higher Accumulation Of Methioninementioning
confidence: 99%
See 2 more Smart Citations
“…Concurrently, an increase of 30% in the concentrations of aspartic acid (Asp) was observed, which severely compromises the nutritional quality of maize [31]. Numerous studies indicate that increasing the levels of Met and Cys in maize can improve their nutritional quality [32,33]. It is argued that an increase in S storage might enhance the concentrations of Met and Cys in maize grains, thereby boosting the nutritional quality of maize grains [34,35].…”
Section: Introductionmentioning
confidence: 99%